Genetics ignite focus on microglial inflammation in Alzheimer's disease. Issue 1 (December 2015) - Malik, Manasi; Parikh, Ishita; Vasquez, Jared; Smith, Conor; Tai, Leon; Bu, Guojun; LaDu, Mary; Fardo, David; Rebeck, G.; Estus, Steven
Abstract In the past five years, a series of large-scale genetic studies have revealed novel risk factors for Alzheimer's disease (AD). Analyses of these risk factors have focused attention upon the role of immune processes in AD, specifically microglial function. In this review, we discuss interpretation of genetic studies.  We then focus upon six genes implicated by AD genetics that impact microglial function:TREM2, CD33, CR1, ABCA7, SHIP1, andAPOE . We review the literature regarding the biological functions of these six proteins and their putative role in AD pathogenesis. We then present a model for how these factors may interact to modulate microglial function in AD.